Future temperature and precipitation projection of the Kelani River Basin in Sri Lanka - Sumanasekara, Harindu Sathsara; Pandey, Vishnu Prasad; Shrestha, Sangam; Duc Hoang Nguyen (Pathum Thani : Asian Institute of Technology, 2017)
Future climate is many location across the globe is projected to change. It may impaction adversely on life and livelihood of people as well as fate of ecosystem. Sri Lanka has faced many problems due to the changing climate in the 21st century. More extreme water events have been observed and more droughts have also appeared in relatively short time intervals. Kelani river basin in Sri Lanka has also faced similar situation. Understanding extent of projected change paves the way for designing adaptation strategies to cope with the changes and associated impacts. The objective of this study is to project future temperature and precipitation in Kelani River Basin, Sri Lanka. Future climate data for the basin was taken from two Regional Circulation Models (RCMs) under two scenarios (i.e., RCP4.5 and RCP8.5). Suitable bias correction technique was adopted to correct RCM based climate data for the base period (i.e., 2006-2015). Results showed that future rainfall increase and temperature is projected to decrease for both mid- and far-future under both the scenarios. For the mid-future (i.e., the 2050s or 2041-2071) precipitation is projected to increase by 12.1 Percent, minimum temperature is projected to decrease by 1.5C and maximum temperature is projected to increase but by 2C.
A capstone project report submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Engineering Civil and Infrastructure Engineering, School of Engineering and Technology
Capstone Project (B.Sc.)-Asian Institute of Technology, 2017
Keywords: Climatic changes -- Sri Lanka -- Kelani River